The mechanisms of ameliorating effect of a green tea polyphenol on diabetic nephropathy based on diacylglycerol kinase α - Hayashi, Daiki (Sci Rep, 2020)
Significant efforts have been made to ameliorate diabetic nephropathy (DN) by inhibiting protein kinase C. However, these efforts have not been successful in human trials, suggesting that novel therapeutic strategies are required. Thus far, it has been reported that green tea polyphenol epigallocatechin gallate (EGCg) improved albuminuria in DN in a human trial. Our previous study revealed that activation of diacylglycerol kinase α (DGKα) plays a crucial role in the amelioration of DN and that EGCg activates DGKα. Here, we investigated whether and how DGKα contributes to the amelioration of DN upon stimulation by EGCg by using streptozotocin-induced type 1 diabetic model mice. Our results revealed that EGCg ameliorated albuminuria in DN through DGKα in vivo, and methylated EGCg, which has higher absorption in the plasma improved albuminuria in DN effectively. Additionally, we showed that c-Src mediated EGCg-induced DGKα translocation and colocalized with the 67 kDa laminin receptor, which is an EGCg receptor. Furthermore, EGCg attenuated the loss of podocytes in DN by preventing a decrease in focal adhesion under high glucose conditions. Our results indicate that the DGKα pathway is an attractive therapeutic target and that activating this pathway is a novel strategy for treating DN.